Sustainable Mariculture Development in Mohéli, Comoros: Gather and analyze environmental and economic prerequisites for different types of mariculture from existing literature to develop scenarios and assess potential implications with local communities - Tamou, Ibrahim (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
Mariculture, or the cultivation of aquatic organisms, holds the potential of enhancing food security, income diversification, and overall economic sustainability. To ensure its growth in the long run, it has to be sustainable particularly from the perspective of local communities, economically profitable, and environmentally friendly. The aim of this paper is to assess the acceptability for the feasibility of potential mariculture development in Mohéli, Comoros, a place with no existing mariculture activity, using Multi-Criteria Decision Analysis (MCDA), scenario planning, and stakeholder preference elicitation. Interviews and focus group discussions were conducted with key stakeholders, including local fishers, lawmakers, and environmental experts, to collect data. The results of the study show that economic gain is the main driving force behind the support for mariculture in the assessed communities, but acceptability is also a function of environmental aspects. Of the many mariculture options, seaweed farming was found to be the most recommendable because of its short harvest period, minimal impact on the environment, and low costs. The study shows that there is a need for specific awareness campaigns, collaborative decision making, and strategically changing management measures to solve ecological and socio-economic problems. The present research can be helpful in this regard as it suggests a method of integrating community interests with scientific decision-making tools to develop a roadmap for the growth of sustainable mariculture while ensuring that there is harmony between social, environmental and economic aspects of development in coastal areas.